ATAC-seq reveals the roles of chromatin accessibility in the chondrocytes of Kashin–Beck disease compared with primary osteoarthritis - Wang, Sen; Wang, Yuanji; Li, Xingyu; Yuan, Linlin; Guo, Xiong; Lammi, Mikko J. (Frontiers in Genetics, 2023)
Objective: We aimed to investigate the roles of accessible chromatin in understanding the different pathogenesis between Kashin-Beck disease (KBD) and primary osteoarthritis (OA). Methods: Articular cartilages of KBD and primary osteoarthritis (OA) patients were collected, and after tissue digestion, primary chondrocytes were cultured in vitro. Assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq) was utilized to compare the accessible chromatin differences of chondrocytes between KBD and OA group. Gene ontology (GO) and KEGG enrichment analyses were executed for the promoter genes. Then, Intact online database was used to generate networks of significant genes. Finally, we did overlap analysis of differentially accessible region (DAR)-associated genes and differentially expressed genes (DEGs) obtained from whole genomic microarray. Results: We obtained 2751 total DARs, which contained 1985 Loss ones and 856 Gain ones and belonged to 11 location distributions. We got 218 motifs associated with Loss DARs, 71 motifs associated with Gain DARs, 30 motif enrichments of Loss DARs and 30 motif enrichments of Gain DARs. 1749 genes are associated with Loss DARs and 826 genes associated with Gain DARs. Among them, 210 promoter genes associated with Loss DARs; 112 promoter genes associated with Gain DARs. We got 15 GO terms of enrichment and 5 terms of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment from Loss DAR promoter genes; 15 terms of GO enrichment and 3 terms of KEGG pathway enrichment from Gain DAR promoter genes. We obtained CAPN6 and other two overlap genes from Loss DARs-vs-down DEGs; AMOTL1 from Gain DARs-vs-down DEGs; EBF3 and other 12 overlap genes from Loss DARs-vs-up DEGs, ADARB1 and other 10 overlap genes from 101 Gain DARs-vs-up DEGs. Overlapping genes were built four gene interaction networks. Conclusion: FGF7, GPD1L, NFIB, RUNX2 and VCAM1 were overlapped genes from the DAR-associated genes and DEGs. These genes were associated with the abnormal of chondrocytes function, which may play crucial roles in the different processes between KBD and OA in the way of accessible chromatin.